Peripheral T cell immune repertoire is associated with the outcomes of acute spontaneous intracerebral hemorrhage - Zhang, Rui; Wang, Li; Zhang, Jiapo; Zhang, Xiufang; Wang, Peng (Frontiers in Neurology, 2024)
Systematic immune responses have been identified in patients with acute spontaneous intracerebral hemorrhage (ICH). T cells have been established to participate in central nervous system damage and repair following brain injury. However, their contribution to the prognosis of patients with ICH remains to be elucidated. In this study, peripheral blood mononuclear cells (PBMCs) were collected from 45 patients with acute spontaneous ICH (<24 h from symptom onset). Our results exposed significant negative correlations between hematoma volume/white blood cell (WBC) density and Glasgow Coma Scale (GCS) score. Contrastingly, lymphocyte density was negatively correlated with hematoma volume and positively correlated with GCS score. Moreover, flow cytometry determined that ICH activated T cells despite their proportion being lower in blood. Afterward, immune repertoire sequencing (IR-seq) revealed a significant decrease in VJ, VDJ usage, and TCR clonotypes in ICH patients. Finally, variations in the complementarity-determining region 3 (CDR3) amino acid (aa) were also detected in ICH patients. This study reveals the occurrence of peripheral T-cell diminishment and activation in response to acute hematoma. ICH lesion also alters the T cell receptor (TCR) immune repertoire, which is associated with patient prognosis.